(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Satisfaction is a major factor for public educational workers. Job happiness is found as an inward feeling generated by multiple factors in the workplace. Owing to the position of diverse factors in work satisfaction, educational institutions must be informed of the correct types of leadership. Owing to the lack of commitment to this organizational activity, some abnormal reactions between workers arise. This paper provides a literature review to define the critical role of leadership types for workers of public education organizations. Substantial consideration should be given to the particular organizational style of an organization. Similarly, unique leadership styles as external influences play a significant part in pleasing workers of public education organizations, and these models may maximize the loyalty of employees to organizations. This program aims to enhance employee loyalty and find an efficient design that is one of the key fields for changing the educational institution.